2002
DOI: 10.1128/jvi.76.6.2730-2738.2002
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Primary CD8+T-Cell Response to Human Immunodeficiency Virus Type 1 Gag and Env Generated by Vaccination with Recombinant Vesicular Stomatitis Viruses

Abstract: We investigated the primary cellular immune responses to human immunodeficiency virus type 1 (HIV-1) Env and Gag proteins elicited by recombinant vesicular stomatitis viruses (rVSVs). The primary response to Env peaked 5 to 7 days after intraperitoneal vaccination, at which time 40% of CD8 ؉ cells were Env tetramer positive and activated (CD62L Lo ). These freshly isolated cells actively lysed target cells pulsed with the p18-I10 peptide and secreted gamma interferon and tumor necrosis factor alpha after stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 52 publications
(51 reference statements)
3
55
0
Order By: Relevance
“…The p18-I10 peptide is presented on several different MHC-I alleles, but it is most efficiently presented on the H-2D d class I molecule. Using H-2D d MHC-I tetramers containing the p18-I10 peptide (MHC-I Env tetramers), we previously showed that vaccination of mice with VSVEnv results in a strong primary response to Env that peaks 5 to 7 days after vaccination (16). The primary response rapidly declines to about one quarter of its peak level by 15 days after vaccination (16).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The p18-I10 peptide is presented on several different MHC-I alleles, but it is most efficiently presented on the H-2D d class I molecule. Using H-2D d MHC-I tetramers containing the p18-I10 peptide (MHC-I Env tetramers), we previously showed that vaccination of mice with VSVEnv results in a strong primary response to Env that peaks 5 to 7 days after vaccination (16). The primary response rapidly declines to about one quarter of its peak level by 15 days after vaccination (16).…”
Section: Resultsmentioning
confidence: 99%
“…Using H-2D d MHC-I tetramers containing the p18-I10 peptide (MHC-I Env tetramers), we previously showed that vaccination of mice with VSVEnv results in a strong primary response to Env that peaks 5 to 7 days after vaccination (16). The primary response rapidly declines to about one quarter of its peak level by 15 days after vaccination (16). The magnitude of the peak primary response prompted us to determine if long-term memory cells specific for the p18-I10 peptide could be detected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the single-cell level, our study did not reveal any enhancement in the frequency of gp120-specific CD8 ϩ T cells in mice immunized with gp120 DNA in the presence and absence of DC expansion in vivo. These assays have proven to accurately measure T cell immune responses elicited by viral infections (47,67) or by the various modes of DNA vaccination (68,69). This could be due to a number of factors.…”
Section: Discussionmentioning
confidence: 99%